Conflicts of interest among dermatology textbook authors - Jorge Roman, MD; David J. Elpern, MD; John G. Zampella, MD (Wolters Kluwer, 2019)
Background: Conflict of interest as it relates to medical education is a burgeoning topic of concern. Dermatology textbooks are an influential resource for dermatologists. This study evaluates industry payments to authors of major dermatology textbooks. Objective: The primary objective of this study is to evaluate whether authors of dermatology textbooks had appreciable conflicts of interest in the form of payments from industry. Methods: This is a retrospective study in which the authors and editors of eight commonly used general dermatology textbooks were entered into the ProPublica Dollars for Docs database to identify industry payments data from 2016. Results: The total compensation for 381 authors in 2016 was $5,892,221. Zero payments were reported for 39.6% of authors. Of the dermatologists, 50%, 66%, 70%, and 81% received less than $100, $500, $1000, and $5000, respectively. The top 10% of dermatologists who collected payments received $5,267,494, which represented 89% of the total payment amount. Limitations: The study was limited to eight textbooks. Data are only as accurate as reported to the Centers for Medicare and Medicaid Services. The database does not include information on dermatologists from non-U.S. institutions. Funding for clinical trials and other avenues of support (e.g., lasers, cosmetic instruments, institutional payments) are also not captured in this database. Conclusion: A minority of authors of influential dermatology textbooks received the lion's share of payments from industry.